CREATIVE AND HEURISTIC ABILITIES OF STUDENTS - Pylnik, E.O. (Pedagogy of Higher and Secondary Education, 2008)
The concept of creative and heuristic activity, creative and heuristic capabilities and their components is examined in this article.